الكنز العربي : التطوير والتنفيذ كتاب المفردات لترقية كفاءة الترجمة عند الطلاب في معهد المودة الإسلامية للبنات فونوروغو - Jamaluddin Shiddiq (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
Based on the problems found by the author in the field (Al-Mawaddah Islamic Boarding School) which include the scarcity of mufradat lessons textbooks, the difficulty of students absorbing new vocabulary and the urgency of preparing thematic mufradat textbooks, this research needs to be done. This study uses a research and development approach, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instrument for measuring variables is the results of the pre-test and post-test of first graders. Based on the results of the pre-test and post-test, this mufradat textbook is known to be very effective in learning Arabic and improving translating skill because there is a big difference between the scores of the pre-test and post-test results and some advice and measurement from validators, but in the future there are things that need to be considered by further researchers, namely the use of samples, exercises, measuring books, and giving movement in each last instance.